Intrauterine growth restriction – part 2. (16th December 2016) - Sharma, Deepak; Farahbakhsh, Nazanin; Shastri, Sweta; Sharma, Pradeep
Abstract: Small for gestational age (SGA) infants have been classically defined as having birth weight less than two standard deviations below the mean or less than the 10th percentile of a population-specific birth weight for specific gestational age, whereas intrauterine growth restriction (IUGR) has been defined as a rate of foetal growth that is less than normal for the population and for the growth potential of a specific infant. SGA infants have more frequent problems such as perinatal asphyxia, hypothermia, hypoglycaemia, polycythaemia and many more when compared with their appropriate for gestational age counterpart. They too have growth retardation and various major and subtle neurodevelopmental handicaps, with higher rates of perinatal and neonatal mortality. With the advent of newer technologies, even though the perinatal diagnosis of these SGA/IUGR foetuses has increased, but still perinatal morbidity and mortality rates are higher than normal foetuses and infants. In this part, we have covered neonatal IUGR classification, postnatal diagnosis, short-term and long-term complications faced by these IUGR infants.